Monopolistic Advantages and the International Operations of Firms: Disaggregated Evidence from U.S.-Based Multinationals - Sleuwaegen, Leo (Journal of International Business Studies, 1985)
The paper presents statistical evidence supporting the proposition that the kind of monopolistic advantage possessed by the firm is decisive as to which form of involvement it will choose to penetrate into foreign markets: exporting versus producing abroad. A decomposition of export flows into exports to affiliates (intra-company trade) and exports to unaffiliated buyers proves to be a crucial element in the empirical test of this proposition.